PASCAD - Physical Activity Study of Children and Adolescents with Disabilities in Perth, Western Australia - Packer, Tanya; Briffa, Tom; Downs, Jennepher; Ciccarelli, Marina; Passmore, Anne (2006)
Physical activity is widely recognised as important for physical and mental health. Studies which have investigated levels of physical activity in children and adolescents have not described the situation for children/adolescents with a disability. The Physical Activity Study of Children and Adolescents with a Disability (PASCAD) was undertaken to examine the physical activity of children/adolescents with a disability in metropolitan Perth, Western Australia. The aims of the PASCAD study were to: provide a baseline measure of the physical activity levels of children/adolescents with a disability in Western Australia; thereby establishing a benchmark against which to measure future interventions; allow comparison to other studies (CAPANS 2003, CLASS 2004) of typical developing peers as well as to the Australian guidelines on physical activity for children; and provide information to the participating community agencies regarding the beliefs about and barriers to physical activity of children/adolescents with a disability and their families.